Study of the Annealing Effects of Sputtered Bi2Te3 Thin Films with Full Thermoelectric Figure of Merit Characterization - Naumochkin, Maksim; Park, Gyu-Hyeon; Nielsch, Kornelius; Reith, Heiko (Physica Status Solidi-Rapid Research Letters, 2022)
Micro-thermoelectric (TE) devices have a great potential for future applications in the field of energy harvesting to power autonomous sensors. Bi2Te3 sputtered at elevated substrate temperatures exhibits a high figure of merit (ZT) suitable for the fabrication of micro-TE devices. However, a lift-off process that does not allow higher substrate temperatures is often used, and although Bi2Te3 is a well-studied TE material, it lacks full ZT characterization of thin films. Herein, the full TE characterization of sputtered Bi2Te3 thin films is presented, including the charge carrier concentration and mobility, which are deposited at room temperature and postannealed between 150 and 300 °C. The influence of the annealing time and temperature is investigated on a 90 nm-thick Bi2Te3 film. A maximum ZT of 0.20 is found, which results from the increasing crystallinity and reduction of point defects. To investigate the thickness dependency, Bi2Te3 films with thicknesses of 90, 170, 350, and 470 nm are annealed at 250 °C. A maximum ZT value of 0.26 is observed for the 350 nm Bi2Te3 film. Furthermore, it can be shown that with increasing film thickness, the annealing time has to be increased to maximize ZT.
CRIS-Team Scopus Importer:2022-04-14
Keywords: annealing effects; Bi; physical vapor deposition; thermoelectric characterizations